Introduction to the use of economic indicators - Doody, Francis S. (New York, Random House, 1965)
This book is designed to provide a kind of wading pool where students can get the feel of the water and some practice in actual strokes. The opportunity in terms of the availability of data and the need in terms of students requirements are both so great that it is odd that a technique of sort presented here has not previously been publicly developed.
aia 28/01/2019
Loans
Keywords: Economic forecasting; Economic indicators